Análisis y diseño de filtros diferenciales basados en líneas acopladas - Sánchez-Martínez, Juan José; Márquez-Segura, Enrique (My University, 2014)
The design of differential bandpass filters using coupled lines is presented. The topology proposed, consisting of short-circuited coupled lines is analyzed by means of analytical equations. The study is carried out by using equivalent circuit models that provide some insights into the physical behaviour of the proposed structure. Furthermore, to increase the bandwidth of the filters, wire-bonded multiconductor transmission lines (MTL) are employed. Three differential filters are designed and fabricated with fractional bandwidths (FBW) of 15%, 120% and 130% (3-dB FBW). The measured differential-mode responses show insertion losses lower than 1 dB with high common-mode rejection levels greater than 20 dB. In addition, there is a very good agreement between the theoretical and experimental results.
Keywords: Radio; Filtro; Líneas acopladas; Diferencial